2012
DOI: 10.1001/archdermatol.2012.509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dermoscopy Education on the Ability of Medical Students to Detect Skin Cancer

Abstract: To determine students' ability to discriminate benign vs malignant lesions and to assess attitudes regarding skin cancer examination (SCE).Design: Second-year medical students at 1 institution participated in an SCE intervention for 2 consecutive years.Intervention: Cohort 1 received intervention A, consisting of SCE teaching without a dermoscopy tutorial. Cohort 2 received intervention B, consisting of SCE teaching with a dermoscopy tutorial, access to online dermoscopy resources, and a dermoscope.Main Outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 34 publications
(29 reference statements)
3
19
0
4
Order By: Relevance
“…In contrast, specificity depends on experience, and it only increased for the most expert users, while dermoscopy led to a decrease in specificity in the group of novices (from 58.6 to 45.6%, p = 0.02). The data demonstrated in the present study support previously published prospective studies where dermoscopy has been shown to improve diagnostic accuracy among well-trained dermatologists [5], and improve detection of skin cancer even among nondermatologists and novices [6][7][8].…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, specificity depends on experience, and it only increased for the most expert users, while dermoscopy led to a decrease in specificity in the group of novices (from 58.6 to 45.6%, p = 0.02). The data demonstrated in the present study support previously published prospective studies where dermoscopy has been shown to improve diagnostic accuracy among well-trained dermatologists [5], and improve detection of skin cancer even among nondermatologists and novices [6][7][8].…”
Section: Discussionsupporting
confidence: 90%
“…namely the heuristic method based on the overall gestalt of a given lesion and the analytic approach based on the description of patterns and specific criteria (clues). It has been shown previously that a short time teaching of dermatoscopy to medical students in general has beneficiary effects to diagnostic accuracy and is superior to mere clinical teaching . In our study, we could reproduce an equal diagnostic improvement compared to the pretest performance status irrespective of the method used for teaching.…”
Section: Discussionsupporting
confidence: 51%
“…Pre- and post-test assessments were accomplished with in-class surveys and image-based tests of 10 lesions immediately prior to the lecture and immediately after delivery of the lecture. The results of these outcomes are discussed elsewhere [5. ]…”
Section: Methodsmentioning
confidence: 99%
“…The continued use of dermoscopy can reduce the number of benign lesions being excised compared to clinical examination alone [3,4]. We have previously shown that incorporating dermoscopy teaching into a medical school curriculum can improve skin cancer detection between two cohorts of second-year medical students; one cohort received dermoscopy training and the other did not [5]. To our knowledge, our study was the first to examine the use of dermoscopy to enhance SCE instruction in the preclinical setting.…”
Section: Introductionmentioning
confidence: 99%